Analisi Metode Pembelajaran Kooperatif Jigsaw Untuk Meningkatkan Keaktifan Dan Hasil Belajar Siswa - Dinda Aulia Rahmi; Jannatul Ma’wa; Jesi Alexander Alim (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Jigsaw is a multifunctional cooperative learning structure. Jigsaw can be used in a number of ways to achieve a variety of objectives but is primarily used for presentation and acquiring new material, this structure creates interdependence. Jigsaw-type cooperative learning is a learning method based on a form of multifunctional structure of learning groups that can be used on all subjects and all levels to develop each group's expertise and skills that they have learned previously at expert team meetings. In the jigsaw type cooperative learning model, there are groups of origin and expert groups. The home group is the parent group of students with diverse abilities, genders and family backgrounds. Expert group, which is a group of students consisting of members of different origin groups, is assigned to study the topic and then explain it to members of the origin group. The expert group is a combination of several experts from the origin group. The key to the success of jigsaw is interdependence, i.e. each student depends on his/her team members to be able to provide the necessary information in order to perform well during the assessment.